"Enneady" Plotyna inspiracją dla św. Jana od Krzyża w nauce o drodze do kontemplacji? - Zarzycki, Stanisław (Verbum Vitae, 2021)
Taking into account the influence of Neoplatonism on Christianity in antiquity and in the Middle Ages, the author asks about the possible influence of Plotinus’ Ennead on the doctrine about the path to contemplation of St. John of the Cross. He first introduces the Plotinian vision of reality, according to which, from one principle, from the One in the process of emanation, beings emerged: mind; the individual soul and the soul of the world. Then it shows man and his return to the Absolute through asceticism, contemplation and Plotinian ecstasy. Analyzing the Enneads of Plotinus and their interpretation in the field of spiritual doctrine in famous commentators (A. Bord, J. Baruzi, M. de la Corte, B. Salmona, L. Bouyer), he compares the descriptions of selected moments of the spiritual path to contemplation and ecstasy in two spiritual masters and interprets them taking into account the doctrinal and spiritual differences between Neoplatonism and Christianity. By identifying the few similarities in the descriptions, especially concerning the way of purification, and taking into account the fundamental and more detailed differences, one inclines with Bord to accept the possible inspiration of Ennead Plotinus only in certain aspects of the description of the spiritual experience of the Carmelite mystic.